2017
DOI: 10.9734/mrji/2017/34085
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Klebsiella pneumoniae -ESBL Producing Strains Isolated from Clinical Specimens in Abidjan (Cote de Ivoire)

Abstract: Aims:The objective of this study is to detect the prevalence of qnr genes in broad-spectrum betalactamase producing Klebsiella pneumoniae, involved in hospital and community-acquired infections. Study Design: It is a retrospective study. Place and Duration of Study: Bacteriology and virology laboratorie of Institut Pasteur, Abidjan, Côte d'Ivoire. Methodology: From January 2011 to June 2016, 350 Klebsiella pneumoniae were isolated from various clinical specimens and identified by conventional bacteriological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
1
5
1
Order By: Relevance
“…Commonly found in E. coli, TEM-1 is able to hydrolyze penicillins and narrow spectrum cephalosporins such as cephalothin (Ur Rahman et al, 2018; Galindo- Méndez, 2020). TEM-1 has also been reported in Côte d'Ivoire from previous studies (Guessennd et al 2008;Tahou et al, 2017) in Klebsiella pneumoniae. According to the scientific literature, the TEM-9 variant is detected for the first time in Côte d'Ivoire.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Commonly found in E. coli, TEM-1 is able to hydrolyze penicillins and narrow spectrum cephalosporins such as cephalothin (Ur Rahman et al, 2018; Galindo- Méndez, 2020). TEM-1 has also been reported in Côte d'Ivoire from previous studies (Guessennd et al 2008;Tahou et al, 2017) in Klebsiella pneumoniae. According to the scientific literature, the TEM-9 variant is detected for the first time in Côte d'Ivoire.…”
Section: Discussionsupporting
confidence: 56%
“…blaTEM, blaSHV and blaCTX-M are the main variants of genes coding for resistance in Enterobacteriaceae with the latest one (Ahmad and Khadija, 2019). In Côte d'Ivoire, recent studies have reported the spread of ESBL-producing strains of E. coli and K. pneumoniae in various infections (Tahou et al, 2017;Gadou et al, 2018) although the setup since 2002 of an observatory of antimicrobial resistance is dedicated to actions contributing to fight against the spread of resistant or multi-resistant bacteria (Ouédraogo et al, 2017). In addition, information on genetic variants and intragenic mutations encoding these resistances are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…QnrB was observed to be co-produced with CTX-M-15 in Algeria strains of E. coli [33]. A similar result was recently found in Klebsiella pneumoniae isolates from Côte d’Ivoire, but the type of ESBL was not determined [24]. Qnr genes are usually found in multi-resistance plasmids linked to other resistance determinants, beta-lactamase genes have been conspicuously common [5, 6, 25, 26].…”
Section: Discussionmentioning
confidence: 75%
“…with 14.6% for qnrB , 9.9% for qnrA and 2.7% for qnrAS [10]. Always in Côte d’Ivoire, others authors found 50.54% of qnr genes in Klebsiella pneumoniae (71.73% qnrB , 26.08% qnrS and 2.17% qnrA ) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Each urine sample was inoculated on the CHROMAgar medium using plastic loops for 10 μl (Ohkusu, 2000 colonies were colored in metallic blue and medium in size (Ohkusu, 2000). Identification of bacterial species was made based on reactions of Gram, morphology and biochemical characteristics using the gallery of the reduced rack of LEMINOR (Urea; Indol; Simmons' citrate agar; Kligler Hajna agar; iron Lysine agar), oxidase and catalase tests (Tahou et al, 2017). Clean catch urine samples were collected from patients and bacteriological analyses were performed using standard microbiological procedures.…”
Section: Isolation and Identification Of Uropathogensmentioning
confidence: 99%